1996
DOI: 10.1002/(sici)1097-0010(199603)70:3<321::aid-jsfa505>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Properties of Apple Pectinesterase

Abstract: Pectinesterase from apple was separated into two fractions by chromatography on Sephadex G‐75. The major pectinesterase was purified by cation‐exchange chromatography on CM‐Sephadex C‐50. It had a molecular mass of 36 kDa, and isoelectric point of about 9, similar to one of the major pectin‐esterases of lemon. The enzyme required the presence of cations for optimum activity and was completely inactive at temperatures above 75°C. Although the major pectinesterase had no effect on the cloud stability of apple ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…The latter also reported that the lower the apple juice pH, the quicker the PPO inactivation. Usually, heat treatment at least at 75°C is required if a fast inactivation of the PME present in the apple juice is desired (Macdonald & Evans, 1996). For example, for heat treatment at 90°C, treatment duration of at least 1 min is needed to inactivate the PME (Castaldo, Quagliuolo, Servillo, Balestrieri, & Giovane, 1989).…”
Section: Effect Of Mild Heat Treatment On Ppo and Pme Activity Of Appsupporting
confidence: 85%
“…The latter also reported that the lower the apple juice pH, the quicker the PPO inactivation. Usually, heat treatment at least at 75°C is required if a fast inactivation of the PME present in the apple juice is desired (Macdonald & Evans, 1996). For example, for heat treatment at 90°C, treatment duration of at least 1 min is needed to inactivate the PME (Castaldo, Quagliuolo, Servillo, Balestrieri, & Giovane, 1989).…”
Section: Effect Of Mild Heat Treatment On Ppo and Pme Activity Of Appsupporting
confidence: 85%
“…Nevertheless, as suggested by our results the inactivation of the enzyme in OMW seems to occur at higher temperatures (like 70-80 C). These values are in accordance with PME activation and inactivation temperatures in other plant sources, where 60 min thermal treatment at 60 C is adequate for endogenous PME activation in green beans and tomatoes (Anthon & Barrett, 2006), while inactivation of isolated banana and apple PME occurs above 70 and 75 C, respectively (Macdonald & Evans, 1996;Nguyen, Van Loey, Fachin, Verlent, & Hendrickx, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Apple PME has a molecular mass of 36 kDa (Macdonald & Evans, 1996) with one subunit (D' Avino, Camardella, Christensen, Giovane & Servillo, 2003). In general, the larger an enzyme and the more complex its structure, the more susceptible it is to high temperature (Yang, Li & Zhang, 2004).…”
Section: Inactivation Of Hpcd and Mh On Ppo And Pme In Cloudy Apple Jmentioning
confidence: 99%